Interpreting Tafel behavior of consecutive electrochemical reactions through combined thermodynamic and steady state microkinetic approaches. Issue 2 (28th January 2020) - Mefford, J. Tyler; Zhao, Zhenghang; Bajdich, Michal; Chueh, William C.
Abstract : A combined DFT and microkinetic model is developed to interpret the experimental oxygen evolution reaction Tafel behavior on CoO x (OH)2− x electrocatalysts. Abstract : Assessing the reaction pathway of multi-electron-transfer reactions is an essential yet difficult task for the rational design of electrocatalysts. In this work, we develop a heuristic approach that combines thermodynamic adsorption energetics calculated through density functional theory with microkinetic modeling using the steady state approximation to interpret the potential-dependent Tafel behavior of consecutive electrochemical reactions. In doing so, we introduce a kinetic framework for ab initio calculations that ensures self-consistent adsorption energetics based on kinetically limited adsorbate coverages. The approach is applied to experimental results on CoO x (OH)2− x single crystal electrocatalyst particles yielding coverage dependent mechanistic information and identification of the rate-limiting step with standard rate constants for the oxygen evolution reaction on the (112̄0) surfaces of the β-Co(OH)2, β-CoOOH, and CoO2 bulk phases. This generalizable method enables catalyst benchmarking based on determining the active species involved and associated intrinsic reaction rate constants in consecutive multi-electron-transfer reactions.